(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article scientifically analyzes the share of small business in gross domestic product (GDP) and its impact on the country’s economic growth. The study examines the experience of developed and developing countries, particularly the indicators of the small business sector in the economy of Uzbekistan. The article quantitatively and qualitatively assesses the contribution of small business to employment, innovation, regional development and export potential. The results of the study can serve as a basis for developing policy recommendations for supporting small business.